Utilization Of Palm Oil Mill Solid Waste And Inorganic Fertilizers On Chinese Kale (Brassica alboglabra) In Ex Coal Mining Soil - Made Deviani Duaja; Elis Kartika; D C Fransisca (Agric, 2020)
The purpose of this experiment is to evaluate the best combination of inorganic fertilizers and organic material from palm oil mill waste decanter cake, which give the best Chinese kale growth and yield at ex-coal mined soils. This is a pot research, conducted at Agricultural Farm, Agriculture Faculty, Jambi University, using RCBD with one factors and 11 treatments of combinations of NPK + Decanter Cake fertilizer from palm oil mill solid waste. The parameters observed were increase in plant height and number of leaves, leaf area and plant fresh weight. The results showed, the best treatments for increasing plant height and number of leaves was achieved at 50% of NPK from recommended doses with DC 20 ton/ha or 75% of NPK with DC 20 tons per hectare. For leaf area and plant fresh weight (yield), was achieved at 50 percent of NPK from recommended doses + DC 15 tons per hectare. The conclusion of this research is to increase chienese kale growth and yield in ex-coal mining soil can be done by fertilizing NPK 50 percent from recommended doses + decanter cake 15 tons per hectare.